Live Streaming, Content Marketing, Flash Sale In Online Shopping Decisions For E-Commerce - Nasrul Efendi; Pioner Pelawi; Anto Tulim (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2024)
This study underscores the pressing need to support the growth and success of e-commerce platforms in addressing the challenges and seizing the opportunities of today's digital commerce landscape. The primary objective of the research is to assess the impact of live streaming, content marketing, and flash sales on the online shopping decisions of users on Tokopedia. The study employs a descriptive statistical analysis, combining qualitative methods with quantitative elements. The research population consists of Tokopedia users in Medan City, with purposive sampling used to select participants. A convenience sampling technique determined the sample size, which included 260 respondents. The results of the study show that content marketing has a significant and notable effect on online shopping decisions, whereas flash sales and live streaming have smaller effects and are not statistically significant.